The coexistence of lichen sclerosus and morphea in the same lesion in a child with insulin dependent diabetes and celiac disease. - Loo, W.J.; Farrell, A.M.; Holt, P.J.A. (European Journal of Pediatric Dermatology, 2000)
We report a 10-year-old Somali child with insulin dependent diabetes and celiac disease, who has clinical and histological features of lichen sclerosus (LS) and morphea co-existing in the same lesion. To our knowledge, this is the first such report in childhood. The close association of LS and morphoea is discussed, as is the link between them and various autoimmune diseases.